2021
DOI: 10.1177/15589447211058838
|View full text |Cite
|
Sign up to set email alerts
|

Wide Awake Local Anesthesia No Tourniquet Technique in Hand Surgery: The Patient Experience

Abstract: Background: We attempted to evaluate patient satisfaction and overall experience during wide awake, local anesthesia, with no tourniquet (WALANT) hand surgery and quantify surgery-related outcomes. Methods: We conducted a retrospective analysis of patient demographics, comorbidities, and patient reported outcomes via Single Assessment Numeric Evaluation (SANE) scores collected pre- and postoperatively of patients undergoing WALANT surgery by the 2 participating senior authors. A solution of 1% lidocaine with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In addition, although no formal cost analysis was performed, the economic burden on the family is clearly alleviated when the additional costs associated with an operating room and staff are removed. Several studies have already proven a significant cost benefit for wide awake local anesthesia no tourniquet surgery when compared with the same procedure performed under general anesthesia 25–28. As such, we feel that the surgeon’s office is the ideal setting for the surgical treatment of infants presenting with this common condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, although no formal cost analysis was performed, the economic burden on the family is clearly alleviated when the additional costs associated with an operating room and staff are removed. Several studies have already proven a significant cost benefit for wide awake local anesthesia no tourniquet surgery when compared with the same procedure performed under general anesthesia 25–28. As such, we feel that the surgeon’s office is the ideal setting for the surgical treatment of infants presenting with this common condition.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already proven a significant cost benefit for wide awake local anesthesia no tourniquet surgery when compared with the same procedure performed under general anesthesia. [25][26][27][28] As such, we feel that the surgeon's office is the ideal setting for the surgical treatment of infants presenting with this common condition.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with our results, study of Lee et al, (8) as they reported that there was no statistically significant difference between WALANT and conventional groups as regard weight. Also, Pina et al, (9) demonstrated that there was no statistically significant difference between both studied groups as regard comorbidities.…”
mentioning
confidence: 84%
“…A simulation recently showed that driving is theoretically not impaired with a bandaged, numb hand 70 . Pina et al reported that 39% of patients admitted having driven to and from the surgical procedure 69 , and a prospective study revealed that 29.5% of patients anonymously reported that they drove the day of the surgical procedure and 51.4% had returned to driving by the end of postoperative day 1 after outpatient hand surgery, regardless of anesthesia type. Thirty-four percent of patients in that study reported returning to driving while wearing a cast, splint, or sling 71 .…”
Section: Practice Managementmentioning
confidence: 99%